(untitled) (Islas, 2026)
Introduction: This study provides an unprecedented in-depth analysis of the anticolonial and counter-hegemonic thought of José Antonio Aponte. It has the distinction of recognizing him as a precursor of the epistemic detachment from Eurocentrism, the first step toward decolonial thinking. Methods: Using a qualitative approach, the study was conducted through ethnographic methods and content analysis, employing triangulation and cross-checking techniques for oral, written, and visual data to ensure the objectivity of the research under examination. Results: Aponte’s Book, begun in 1806 and seized in 1812, systematized a principle of resistance against colonial power. It challenged the symbolic system of Eurocentric hegemonic culture. He established his own pictorial-political-educational corpus and recontextualized African-rooted ethnic heritages within the visual imaginary of power. Conclusions: José Antonio Aponte developed an innovative program of universal cultural historical memory. He subverted Eurocentric hegemony through cultural and ethnic diversity and gender equity, denaturalizing the prevailing relations of oppression within the symbolic world.